(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Sulphur is a component of plant amino acids, proteins, vitamins, and enzyme structures which influence the productivity of oil seed and total oil content. The experiment was conducted to find out the effect of sulphur on the seed yield and oil content of sesame in Bangladesh. The experiment comprised three varieties of sesame viz. Binatil-2, Binatil-3 and BARI Til-4 and six levels of sulphur (S) viz. 0, 10, 20, 30, 40 and 50 kg S ha–1. The experiment was laid out in a randomized complete block design with three replications. Dry matter production, crop characters, yield components, seed yield and oil content were significantly influenced by variety, level of sulphur and their interaction. The highest dry matter production plant–1 at 50 DAS (17.56 g), plant height (101.3 cm), number of branches plant–1 (3.66), number of pods plant-1 (41.56), number of seeds pod-1 (58.83), seed yield (747.2 kg ha-1), stover yield (2243.0 kg ha–1) and oil content (40.03%) were obtained in BARI Til-4 while the corresponding lowest values of all parameters were recorded in Binatil-2. In case of sulphur application, the highest dry matter production plant–1 at 50 DAS (20.81 g), plant height (109.7 cm), number of branches plant–1 (3.87), number of pods plant–1 (46.13), number of seeds pod-1 (56.67), seed yield (800.0 kg ha–1), stover yield (2787 kg ha–1 ) and oil content (43.97%) were obtained when crop was fertilized with 30 kg S ha–1 while the lowest seed yield (502.2 kg ha–1), stover yield (1550.0 kg ha–1) and oil content (32.80%) were obtained in control (0 kg S ha–1). BARI Til-4 fertilized with 30 kg S ha–1 produced the highest dry matter plant–1 at 50 DAS (24.80 g), number of pods plant–1 (51.13), seeds pod–1 (62.0) and seed yield (1011.0 kg ha–1). The highest oil content (43.97%) was also recorded in BARI Til-4 fertilized with 30 kg S ha–1, which was as good as that of BARI Til-4 fertilized with 40 kg S ha–1. Therefore, BARI Til-4 fertilized with 30 kg S ha–1 can be considered as a promising practice in respect of seed yield and oil content of sesame in Bangladesh. J. Bangladesh Agril. Univ. 17(1): 33–38, March 2019